Enhancing the removal of total dissolved solids from petroleum wastewater through electrocoagulation - Muhammad Jasim; Forat AlJaberi; Saja Alardhi; Ali Salman; Mustafa Hathal; Igor Cretescu; Armando Vargas (Engineering and Technology Journal)
This study aims to employ an electrocoagulation reactor to treat petroleum effluent from a local plant and reduce dissolved solids (TDS) to suitable levels for reuse. A continuous reactor configuration featured a finned stainless steel cathode tube positioned between two cylindrical aluminum anodes. This study explored the influence of treatment duration (4–60 minutes), current density (0–6.0 mA.cm-2), and influent rate (50–150 ml/min) on the final TDS value. Flow rate increase correlated with increased final TDS values, while longer electrolysis durations and higher current densities led to decreased TDS levels. Optimized electrolysis conditions at 1 hour, 5 mA.cm-2, and 50 ml/min, with inner and outer anode consumptions of 0.18 g and 0.45 g, respectively, achieved a final TDS of 2000.45 mg/l, representing a reduction of 207.55 mg/l. The regression model, with a p-value of 0.0001, F-value of 219.37, and R2 of 99.75%, demonstrated the significance of the model components, indicating its robustness. The energy consumption was 3.65 kWh/m3, and the total operating cost was only 0.74 $ per m3. This study confirms the efficacy of the novel continuous reactor in managing petroleum wastewater under practical conditions with low consumption values of electrodes and electrical energy.